A Content Analysis of Modals in Action Pack Ten, Eleven, Twelve in Terms of Variety in Meaning, Distribution, and Activities: Recommendations for Effective Methods in Teaching Modals: Recommendations for Effective Methods in Teaching Modals - Najat Ahmed Busabaa; Najla Abdullah Ateeg (University of Muhammadiyah Prof. DR. HAMKA, 2020)
This study aims at investigating the extent to which modals are presented in Action Pack Ten, Eleven, and Twelve in terms of variety in meaning, distribution, and activities which teach students modals and how these activities are effective. The researchers adopt content analysis method to answer the question of the study. The unit of analysis is the modal verb in Action Pack Ten, Eleven, and Twelve. They categorized modals in terms of the type of modality they express into: modals that indicate deontic modality, modals that indicate epistemic modality, and modals that indicate dynamic modality. Each category will be subcategorized according to the specific meaning it indicates such as: possibility, ability, permission, obligation, and advisability. The findings of the study revealed that the most dilemmatic issue in teaching modals is their meanings due to the fact that students are, sometimes, overwhelmed by the idea that there is only one meaning for each modal whatever it occurs in different contexts. Thus, they should be acquainted with the opposite idea, i.e., each modal has more than one meaning according to the context it occurs in. Key Words: content analysis, modals, Action Pack Ten, Eleven, Twelve, meaning, distribution, and activities, effective methods in teaching modals